Strategi Guru PPKn dalam Mengelola Kelas Pada Mata Pelajaran Pendidikan Pancasila di Kelas VII SMP Negeri 8 Gorontalo - Indri Asraini La Punu; Ngiu, Zulaecha; Adjie, Zulfikar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2026)
Social change and technological development place education in a strategic position for shaping citizens’ character based on Pancasila values. The success of Pancasila Education learning is greatly influenced by teachers’ ability to manage the classroom effectively. This study aims to analyze the strategies employed by Pancasila Education teachers in managing classrooms for seventh-grade students at SMP Negeri 8 Gorontalo and to identify the inhibiting factors encountered during the learning process. This research employed a qualitative approach with a descriptive-analytical design. The research informants consisted of three Pancasila Education teachers and ten seventh-grade students selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, and then analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that teachers implement various classroom management strategies, including democratic, inclusive, constructivist, positive, and proactive approaches, to create a participatory and conducive learning environment. However, classroom management still faces several challenges originating from teacher-related factors, such as limited variation in teaching methods and pedagogical competence, as well as student-related factors associated with discipline and learning responsibility. This study confirms that adaptive and humanistic classroom management strategies play a crucial role in enhancing student learning engagement while supporting the internalization of Pancasila values in the learning process